The Effect Of Duolingo Application Toward Students Listening Achievement Of Seventh Grade Students At SMP Negeri 1 Pasaributobing - Tampubolon, Sahlan; Manalu, Axnes Monica; Simarmata, Rina Octavia (Lembaga Riset dan Inovasi Almatani, 2024)
This study focused on finding out the effect of applying Duolingo Application on students listening anchievement. The objective of the study is to find out whether Duolingo Application affects student achievement in listening. This study was conducted by applied experimental quantitative research. The sample of the study was the first-year students of SMP Negeri 1 Pasaributobing. The writer took VII-A which consists of 29 students as an experimental class with used Duolingo Application and VII-B which consists of 29 students as the control group used the conventional method. The population of this study was 58 students which consist of Seventh classes. The writer took two classes as random sampling to see the effect of Duolingo Application as a media in teaching listening. The data were taken by giving listening test. The tests were divided into two tests: pre-test and post-test for both experimental and control groups. The mean score of pre-test in the experimental class is 49,6 and the post-test is 80,5. The mean score of pre-test in the control group is 50,1 and the post-test is 60,5. The result that t-calculated >t-table as the level of significance p =0,05 (18,33 > 1.673). The Alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It is suggested that teachers of English subject apply Duolingo Aplication as an alternative teaching media to help listening ability at seventh grade students of Junior High School.